Eukaryotes may play an important ecological role in the gut microbiome of Graves’ disease - Geng, Xiwen; Liu, Yalei; Xu, Wenbo; Li, Gefei; Xue, Binghua; Feng, Yu; Tang, Shasha; Wei, Wei; Yuan, Huijuan (Frontiers in Immunology, 2024)
The prevalence of autoimmune diseases worldwide has risen rapidly over the past few decades. Increasing evidence has linked gut dysbiosis to the onset of various autoimmune diseases. Thanks to the significant advancements in high-throughput sequencing technology, the number of gut microbiome studies has increased. However, they have primarily focused on bacteria, so our understanding of the role and significance of eukaryotic microbes in the human gut microbial ecosystem remains quite limited. Here, we selected Graves’ disease (GD) as an autoimmune disease model and investigated the gut multi-kingdom (bacteria, fungi, and protists) microbial communities from the health control, diseased, and medication-treated recovered patients. The results showed that physiological changes in GD increased homogenizing dispersal processes for bacterial community assembly and increased homogeneous selection processes for eukaryotic community assembly. The recovered patients vs. healthy controls had similar bacterial and protistan, but not fungal, community assembly processes. Additionally, eukaryotes (fungi and protists) may play a more significant role in gut ecosystem functions than bacteria. Overall, this study gives brief insights into the potential contributions of eukaryotes to gut and immune homeostasis in humans and their potential influence in relation to therapeutic interventions.